Multiple low-dose radiation ameliorates type-2 diabetes mellitus via gut microbiota modulation to activate TLR4/MyD88/NF-κB pathway - Lijing Qin; Rongrong Liu; Zhen Jia; Weiqiang Xu; Li Wang; Hongyuan Tian; Xinru Lian; Wen Li; Yali Qi; Huan He; Zhicheng Wang (BMC Endocrine Disorders)
Abstract Background Type 2 diabetes mellitus (T2DM) is the fastest-growing metabolic disease in the world. The gut microbiota is linked to T2DM. Recent studies have showed that the metabolism of gut microbiota can trigger T2DM. Low dose radiation (LDR) has been proved to activate various protective bioeffects on diabetes. However, the underlying mechanisms remain unclear. Methods In this study, T2DM model was established using high fat diet combined with streptozocin (STZ) injection in C57BL/6 mice, and then exposed to multiple 75 mGy LDR every other day for one month. The changes of blood glucose levels, body weight, and the damage of pancreas were measured. In addition, 16 S rDNA amplicon sequencing was used to detect gut microbiota alteration. Metabolic profiling was carried out using the liquid mass spectrometry system, followed by the combinative analysis of gut microbiota alteration. Furthermore, the inflammatory factors and related pathways were detected. Results We found that LDR attenuate blood glucose levels and the weights of body in T2DM mice, and reduce pancreas impairment. In addition, in the gut, LDR regulated the relative abundance of Bacilli, Desulfobacterota, Verrucomicrobiota, and Proteobacteria. The non-target metabolomics analysis found that LDR significantly improve the metabolic abnormalities in T2DM, which is closely related to the gut microbiota abundance. Furthermore, the inflammatory effects activated by TLR4/MyD88/NF-κB pathways in T2DM were ameliorated by LDR. Conclusion These results suggest that LDR may exert a beneficial role in T2DM by modulating gut microbiota and metabolites, especially in TLR4/MyD88/NF-κB pathway.